Polymorphisms of SLC22A9 (hOAT7) in Korean Females with Osteoporosis - Ahn, Seong Kyu (Korean J Physiol Pharmacol, 2015)
Among solute carrier proteins, the organic anion transporters (OATs) play an important role for the elimination or reabsorption of endogenous and exogenous negatively charged anionic compounds. Among OATs, SLC22A9 (hOAT7) transports estrone sulfate with high affinity. The net decrease of estrogen, especially in post-menopausal women induces rapid bone loss. The present study was performed to search the SNP within exon regions of SLC22A9 in Korean females with osteoporosis. Fifty healthy controls and 50 osteoporosis patients were screened for the genetic polymorphism in the coding region of SLC22A9 using GC-clamped PCR and denaturing gradient gel electrophoresis (DGGE). Six SNPs were found on the SLC22A9 gene from Korean women with/without osteoporosis. The SNPs were located as follows: two SNPs in the osteoporosis group (A645G and T1277C), three SNPs in the control group (G1449T, C1467T and C1487T) and one SNP in both the osteoporosis and control groups (G767A). The G767A, T1277C and C1487T SNPs result in an amino acid substitution, from synonymous vs nonsynonymous substitution arginine to glutamine (R256Q), phenylalanine to serine (F426S) and proline to leucine (P496L), respectively. The Km values and Vmax of the wild type, R256Q, P496L and F426S were 8.84, 8.87, 9.83 and 12.74 µM, and 1.97, 1.96, 2.06 and 1.55 pmol/oocyte/h, respectively. The present study demonstrates that the SLC22A9 variant F426S is causing inter-individual variation that is leading to the differences in transport of the steroid sulfate conjugate (estrone sulfate) and, therefore this could be used as a marker for certain disease including osteoporosis.